Mediating role of work-family enrichment in relationships between individual, job, and organizational factors, and job satisfaction among teachers - Ng, Swee Fung (2013)
Studies on job satisfaction have focused mainly on the direct relationships of antecedent factors on job satisfaction. However, few studies have focused on the role of workfamily enrichment as a mediator. Therefore, it is timely and necessary to examine the role of work-family enrichment acting as a mediator in the relationships between individual, job and organizational factors, and job satisfaction of school teachers, using the theory of conservation of resources, the model of work-family enrichment and the social exchange theory. The specific objectives of the study are to determine (i) the relationships between individual factors (optimism, self-efficacy) and work-family enrichment, and job satisfaction (ii) the relationships between job factors Gob autonomy, job involvement) and work-family enrichment, and job satisfaction; (iii) the relationships between organizational factors (supervisor support, co-worker support) and work-family enrichment, and job satisfaction; (iv) the role of work-family enrichment as a mediator of the relationships between individual factors, job factors and organizational factors, and job satisfaction. Teachers are chosen because teaching is one of the biggest professions in Malaysia and teachers are very influential in the education of students. This study was conducted on teachers from secondary schools in the Bangsar Zone, Kuala Lumpur Federal Territory. Data were gathered from 280 secondary school teachers through the drop and collect method using self-administered questionnaires. The data were analyzed using structural equation modeling (SEM) technique which enables the testing of multiple relationships simultaneously. The findings revealed that there were significant positive relationships between self-efficacy, job autonomy, job involvement and co-worker support with work-family enrichment. Work-family enrichment, self-efficacy, job autonomy, job involvement and co-worker support were significantly positive related to job satisfaction. The findings also revealed that work-family enrichment mediated the relationships between self-efficacy, job autonomy, job involvement and co-worker support, and job satisfaction. However, work-family enrichment did not mediate the relationships between optimism and supervisor support, and job satisfaction. The findings of the . study contribute to the body of knowledge on employees' behavior by providing a mediation model which includes work-family enrichment to understand further the phenomenon of job satisfaction. The findings also serve as evidence that the individual factor, namely self-efficacy, job factors that encompass job autonomy and job involvement, and support from co-workers as well as the experience of work-family enrichment can increase the level of job satisfaction. Schools may need to focus on work-family enrichment as the mechanism to promote job satisfaction among teachers.